Correlation Between Vital Signs and Amount of Hemoperitoneum in Ruptured Ectopic Pregnancy - Baniya Chhetri, Puja; Pathak, Priya; Shrestha, Buddhi Kumar; Shrestha, Rubina; Acharya, Manisha; Shrestha, Subha (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Ectopic pregnancy is a life threatening emergency in first trimester of pregnancy. Hemodynamic stability of the patient remains one of the crucial factors that determine the treatment modalities. The main objective of this study was to study the correlation between the vital signs and amount of hemoperitoneum in ruptured ectopic pregnancy so that early and active interventions can be done. Methods: We conducted a cross sectional study of all the pregnant women with ruptured ectopic pregnancy with hemoperitoneum who presented to the emergency department of College of Medical Sciences Teaching Hospital from time period of 1st May 2017-31st May 2020.The different vital signs present at the time of initial emergency department and preoperative period prior surgery were reviewed and used for correlation with amount of hemoperitoneum by using Pearson correlation analysis. Results: A total of 61 patients were studied. Pearson correlation between different vital signs and amount of hemoperitoneum were: heart rate(r=0.48, p<0.001), systolic blood pressure(r= -0.41,p=0.001), diastolic blood pressure (r= -0.34,p=0.06), mean arterial pressure (r= -0.37,p=0.03), respiration rate (r= 0.33, p=0.08) temperature (r=0.09,p=0.94), and shock index (r=0.55,p<0.001). Only 19 of 36 patients with hemoperitoneum ≥750 ml had HR≥100 beats/min and 8 patients had SBP≤90mmHg. Conclusions: None of the vital signs showed strong association with the amount of hemoperitoneum. If decision for surgical interventions were made based on hemodynamic instability, most of the patients would have been over-diagnosed and treated differently. Proper and timely diagnosis with immediate management should be done.